Astronomer and Surveyor Anton Shahin (1799–1842) - Klimka, Libertas (Lietuvos istorijos studijos, 2023)
The paper presents a new data on the biography of eminent astronomer and land surveyor of Vilnius and Kharkiv universities Anton Szahin (1799– 1842). He was born in Vilnius; may be the scientist was in relationship with Tatar poet Franciszek Szahin-Sokol. A. Szahin studied at the Teachers Institute of Vilnius University. In 1816 he obtained the degree of Master of Philosophy and in next year was invited to work at the Astronomical Observatory of Vilnius University. The Chair of Land Surveying was set up in 1826 and A. Szahin, the author of the first textbooks on higher geodesy (Higher Geodesy and Land Surveying and Levelling, 1929, in Polish) was elected its head. In 1832 the Russian government closed the Vilnius University, as an act of repression after the uprising. A. Szahin was forced to go to Vitebsk where he delivered mathematics at gymnasium. In 1834 A. Szahin was invited to Kharkiv University where he gained the professorship of astronomy.